National screening for phenylketonuria, congenital hypothyroidism and congenital adrenal hyperplasia. - Osório, R V; Vilarinho, L; Soares, J P (Acta Médica Portuguesa, 1992)
In Portugal the screening for phenylketonuria (PKU) and congenital hypothyroidism (CH) was begun towards the end of 1979, and by 1990 59 cases of PKU and 227 cases of CH had been detected. The early initiation of treatment and the observed mental and motor development, point towards a normal development in these children. A trial screen for congenital adrenal hyperplasia was carried out in 100.000 newborns, from which it was concluded that, under the present conditions, screening at a national level is not justified. A similar study is currently being undertaken for biotinidase deficiency and cystic fibrosis. The results ares discussed, as are the cost/benefits evaluations.